Interstellar. - Nolan, Christopher, 1970-; McConaughey, Matthew, 1969-; Hathaway, Anne, 1982- (Hollywood, CA : Paramount Pictures Corporation; Warner Bros. Pictures, 2015)
With our time on Earth coming to an end, a team of explorers undertakes the most important mission in human history; traveling beyond this galaxy to discover whether mankind has a future among the stars.
Matthew McConaughey, Anne Hathaway, Jessica Chastain, Bill Irwin, Ellen Burstyn, Michael Caine./ Originally released as a motion picture in 2014./ Wide screen./ Audience: MPAA rating: PG-13; for some intense perilous action and brief strong language.
Keywords: Adventure films; Science fiction films